The Utilization of Free Online Machine Translation as a Language Learning Tool in Efl Classroom - Dian Saputra; Haryanto Atmowardoyo; Kisman Salija (Institute of Computer Science (IOCS), 2022)
This investigation was aiming to find out how students utilize Free Online Machine Translation (FOMT), and the reasons understudies utilize FOMT as a language-learning tool in perusing the scholarly article. The researcher applied descriptive qualitative research. These inquiries were conducted within the apprentice level of English learners. The members of this survey were 10 students. All of them were selected for the purpose of research. The observation took notes and video records were used to figure out who was using FOMT while reading the scholarly paper. Meanwhile, the interview section was presented with details about the reasons for students introducing the FOMT. The results of this study have shown that the participants employ FOMT as a reading tool in a number of different ways for the period of reading the scholarly paper. These approaches were divided into three parts; first, a word-to-word translation was used by six participants; second, a sentence-to-sentence translation was completed by six participants. Then, what is the frequency used by participants while assessing the FOMT types. In addition, there have been numerous reasons for participants using FOMT to support comprehension of the scholarly paper